ANALISIS PELAKSANAAN PEMBELAJARAN MEMBACA PERMULAAN SISWA BERKEBUTUHAN KHUSUS DI KELAS RENDAH MINU ISLAMIYAH KECAMATAN ASEMBAGUS KABUPATEN SITUBONDO - Fasica, Nani Farah; Hafidayah, Azul; Aminurrahman, Risky (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research aims to investigate learning activities in reading for students with special needs of lower class at MINU Islamiyah Kecamatan Asembagus Kabupaten Situbondo. This study engaged qualitative reserach approach, whreas researcher collected data using observation, interview, and documentation. analysis used was descriptive qualtative research, consisted of data collection, data reduction, and conlusion. The results of the study show that children with spesial needs require different tratment compared to normal students, on of wich requires a companion teacher to provide services for early reading learning activities. teachers must have a extraordinary educational background and must understand the characteristics of students wit spasicial needs. Students with spesial are children who in their development have disoders and obtacies. Thereby, their growt is different to normal children. Physical and psychological disordes, anmely mental, sensory motor, communication disorders, social behavior disorders, and learning difficulties